(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: A migraine is a headache that can cause intense throbbing pain or a pulsing feeling usually on one side of the head and Tension Type Headache (TTH) is a neurological characterized by headache attacks ranging in severity from mild to moderate dull aching bitalteral pain around the temporal region feeling not onlike a pressing or tightening band around the forehad, neck, shoulder and sometimes be hind the eyes. The purpose of the study was to explore prevalence and pattern of migraine and Tension Type of Headache (TTH) and its’ association with depression among medical students at Chattagram Maa-O-Shishu Hospital Medical College. Materials and methods: This cross sectional study included students of 1st year to 5th year which comprises 560 students. Among them 500 students answered a questionnaire from January to July 2024. The Students’’ symptoms were classified as migraine or tension-type headache by the principal author according to the 2nd Edition of International Classification of Headache Disorders II criteria and students’ depression was identified by PHQ questionnaire. Results: The prevalence of headache among students was 71.6%. The prevalence of Migraine, and both migraine and TTH were 26.81%, 20.25% and 12.29% respectively. Compared to male students (42.45%), female students (57.54%) experienced headache much more frequently. Stress (74.86%) and lack of sleep (75.13%) were the leading triggering factors. About half of the students (54.6%) had mild to severe degree of depression and this depression is statistically significant with headache (p=0.000) Conclusion: Our study has shown that relatively large percentage of medical students suffer from headache which was more frequent among female. Migraine and Tension Type of Headache (TTH) were more prevalent than other types. Mild to severe degree of depression was observed among the students. There is a strong association between depression and migraine and TTH. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 20-25